2020
DOI: 10.3389/fonc.2020.578895
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics Feature Activation Maps as a New Tool for Signature Interpretability

Abstract: IntroductionIn the field of personalized medicine, radiomics has shown its potential to support treatment decisions. However, the limited feature interpretability hampers its introduction into the clinics. Here, we propose a new methodology to create radiomics feature activation maps, which allows to identify the spatial-anatomical locations responsible for signature activation based on local radiomics. The feasibility of this technique will be studied for histological subtype differentiation (adenocarcinoma v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…Vuong et al [ 34 ] created a radiomics feature activation map in CT images of non-small-cell lung cancer by comparing whether the feature value from a small patch was higher than the population median feature value from the entire tumor or not, aiming to track the spatial location of regions responsible for signature activation. They found that the texture feature GLSZM_zone size non-uniformity normalized was more activated on the adjacent region of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Vuong et al [ 34 ] created a radiomics feature activation map in CT images of non-small-cell lung cancer by comparing whether the feature value from a small patch was higher than the population median feature value from the entire tumor or not, aiming to track the spatial location of regions responsible for signature activation. They found that the texture feature GLSZM_zone size non-uniformity normalized was more activated on the adjacent region of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, when compared to other quantification-based nomograms ( 14 17 ), the predictor variables in our nomogram are easily accessed and interpreted. In general, lack of interpretability is one of the major barriers to successful translation of predictive models from research to clinical practice, particularly for data-driven precision medicine ( 20 ). From a clinical perspective, interpretability is critical for winning the trust of physicians, developing a robust decision-making system, and overcoming regulatory concerns ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…These models have been developed to mine high-throughput quantitative image features fusing image pixels and morphology through machine learning methods to improve cancer diagnosis and prognosis ( 18 ). However, to varying degrees, reproducibility of quantification features derived from image pixels is sensitive to image preprocessing ( 19 ), particularly for US technology, which has the distinct inherent characteristic of operator- and device-dependent, not to mention that such pixel-based features often lack interpretability ( 20 ). This may lead to limitations in usability for real end-users, impeding their large-scale clinical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Beaumont et al 19 used a random forest approach to predict local recurrence from baseline images thanks to locally calculated features and voxel-wise ground truths. Vuong et al 20 investigated patch-based radiomics with binary activation for tracing the spatial location of regions responsible for a given classification. To the best of our knowledge, although engineered radiomics is largely used especially when datasets are not amenable to deep radiomics, no approach has been proposed to quantitatively map, at the voxel level, the output of a model based on engineered radiomic features.…”
Section: Introductionmentioning
confidence: 99%
“…used a random forest approach to predict local recurrence from baseline images thanks to locally calculated features and voxel‐wise ground truths. Vuong et al 20 . investigated patch‐based radiomics with binary activation for tracing the spatial location of regions responsible for a given classification.…”
Section: Introductionmentioning
confidence: 99%